Discrete modeling of the crushing of nomex honeycomb core and application to impact and post-impact behavior of sandwich structures - Castanie, Bruno; Aminanda, Yulfian; Barrau, Jean-Jacques; Thevenet, Pascal (Springer Science+Business Media Dordrecht, 2012)
In this chapter, an original method for modeling the behavior of sandwich structures during and after impact is proposed and validated. It is based on the demonstration that Nomex honeycomb behaves in a post-buckling mode very early and that compression forces are taken up by the corners or vertical edges of the honeycomb cells in the same way as they are in the stiffeners in aircraft structures. Thus it is possible to represent the honeycomb discretely by a grid of springs located at the six corners of hexagonal cells. This approach represents the phenomenon of indentation on honeycomb alone or on sandwiches very well. This approach provides an understanding of how the sandwich and the core behave under compression after impact. An original criterion based on a local core crush is tested and validated to compute the residual strength. To consider the bending response of sandwich structures, a multi-level approach is also proposed.